Reconfiguring the Category of 'Sudan' through the Literary Field: Representation, Disposability, Ambiguity and the 'Magical' in Four Post-colonial Novels (2002-2022) - Farahat, Mourad (AUC Knowledge Fountain, 2026)
In this thesis I shall argue that contemporary African literature, with ‘’both its ethnographic imagination and anthropological complexity’’ (Orock, 2022, p.3), its use of ‘disruptive’ characters, and its focus on the embeddedness of the ‘collective’, the ‘common’ and the ‘vulgar’ in the personal (Mbembe, 2003), may help us mitigate some social scientific limitations on the study of Africa, and may aid us in understanding relations of power within the post-colony. I seek to show how contemporary Sudanese literature has already moved beyond the fixed social categories, lines, and limits which dominate some of the social scientific literature on Sudan. Literature is capable of moving beyond static limits, lines and social categories, by passing ‘’through the finite in order to rediscover, to restore the infinite’’ (Deleuze & Guattari, 1994, p.197).In this thesis I seek to answer a central question: what can novels tell us about the social production of difference and particularly the limits of social categories such as class, ethnicity, and race, in times of accumulation-driven civil wars and political repression, when all the lines seem to have been removed? I seek to understand how the novels depict the production of social categories, since much of the critical literature emphasizes the relationship between social categories, nation-building, violence and capital accumulation (Roitman, 1998; Braidotti, 2005; Hoffman, 2011a; Alliez & Lazzarato, 2016; The New Socialist, 2022). Here we would also avoid understanding the African warscape in terms of ‘African culture’ or a unique geographical endowment (Hoffman, 2011a). Rather, this should demonstrate how Sudan and Africa are embedded in a global governmentality which is characterized by decentralized counter-insurgency tactics, violence as a form of labour and annihilation, corporate rule and a frenzied drive for resource extraction and accumulation. In addition, I seek to address two other related secondary questions: how do geographical locations relationally appear in the novels and what are their specific socio-historical processes? How do these novels imagine issues such as sovereignty, global governance, civil war, disposability, policing, and possibility? I shall focus on four post-colonial novels, their events taking place between the years 2002-2012, and hence covering the first decade of the twentieth century, from four distinct geographical locations (Kordofan, Gedaref and its vicinity, Khartoum and Darfur). The novels are ‘Ghost Season’ (Abbas, 2023), ‘The Jungo’ (Sakin, 2015), ‘Grub Hunter’ (Tag el-Sirr, 2012) and ‘Masıḥ̄ Dārfūr’ (Sakin, 2014). Taking my cue from Iser (1997), Fluck (2002), Markowski (2012), Oladosu (2024) and Deleuze & Guattari (1994), I seek to show how literature and ‘art’ are forms of thought that should be entitled and encouraged to enter into conversation with other disciplines. I shall argue that the novels selected, as modalities of research, are cognizant of social life, political structures, ‘counterpoints’ and the shifting identities of post-colonial modernities.